Sustained impact of electronic alerts on rate of prophylaxis against venous thromboembolism - Beeler, Patrick Emanuel; Kucher, Nils; Blaser, Jürg (Thrombosis and Haemostasis, 2011)
Advanced electronic alerts (eAlerts) and computerised physician order entry (CPOE) increase adequate thromboprophylaxis orders among hospitalised medical patients. It remains unclear whether eAlerts maintain their efficacy over time, after withdrawal of continuing medical education (CME) on eAlerts and on thromboprophylaxis indications from the study staff. We analysed 5,317 hospital cases from the University Hospital Zurich during 2006–2009: 1,854 cases from a medical ward with eAlerts (intervention group) and 3,463 cases from a surgical ward without eAlerts (control group). In the intervention group, an eAlert with hospital-specific venous thromboembolism (VTE) prevention guidelines was issued in the electronic patient chart 6 hours after admission if no pharmacological or mechanical thromboprophylaxis had been ordered. Data were analysed for three phases: pre-implementation (phase 1), eAlert implementation with CME (phase 2), and post-implementation without CME (phase 3). The rates of thromboprophylaxis in the intervention group were 43.4% in phase 1 and 66.7% in phase 2 (p<0.001), and increased further to 73.6% in phase 3 (p=0.011). Early thromboprophylaxis orders within 12 hours after admission were more often placed in phase 2 and 3 as compared to phase 1 (67.1% vs. 52.1%, p<0.001). In the surgical control group, the thromboprophylaxis rates in the three phases were 88.6%, 90.7%, 90.6% (p=0.16). Advanced eAlerts may provide sustained efficacy over time, with stable rates of thromboprophylaxis orders among hospitalised medical patients.
Keywords: Clinical decision support systems; computerised medical records systems; venous thromboembolism/prevention & control; software; reminder systems